2011
DOI: 10.1111/j.1745-9125.2011.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Be Bad: Adverse Social Conditions, Social Schemas, and Crime*

Abstract: In this paper we develop and test a new approach to explain the link between social factors and individual offending. We argue that seemingly disparate family, peer, and community conditions lead to crime because the lessons communicated by these events are similar and promote social schemas involving a hostile view of people and relationships, a preference for immediate rewards, and a cynical view of conventional norms. Further, we posit that these three schemas are interconnected and combine to form a crimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
228
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(238 citation statements)
references
References 93 publications
8
228
0
2
Order By: Relevance
“…Coefficient alpha for each wave were as follows: wave 1, .78; wave 2, .59; wave 3, .67; wave 4, .44. This measure has been used in a number of past studies to assess delinquency and crime within this age range (Simons and Burt 2011;Burt et al 2012;Su et al 2011). …”
Section: Delinquencymentioning
confidence: 99%
“…Coefficient alpha for each wave were as follows: wave 1, .78; wave 2, .59; wave 3, .67; wave 4, .44. This measure has been used in a number of past studies to assess delinquency and crime within this age range (Simons and Burt 2011;Burt et al 2012;Su et al 2011). …”
Section: Delinquencymentioning
confidence: 99%
“…At least 13 recent studies document a link between individual experiences with racial discrimination and concurrent or subsequent offending. These studies find that interpersonal racial discrimination is associated with self-reported conduct problems (Brody, et al, 2006;DuBois, Burk-Braxton, Swenson, Tevendale, & Hardesty, 2002;Nyborg & Curry, 2003;Simons & Burt, 2011;Simons et al, 2003), violence (Caldwell, Kohn-Wood, Schmeelk-Cone, Chavous, & Zimmerman, 2004;Simons, Simons, & Burt, 2006;Stewart & Simons, 2006), delinquency (Burt et al, 2012;Martin, et al, 2011;Unnever, Cullen, Mathers, McClure, & Allison, 2009), and official reports of arrest (McCord & Ensminger, 1997. A number of different measures of discrimination are used, but all ask the respondents to report whether they have experienced one or more negative acts because, from their perspective, they are black.…”
mentioning
confidence: 96%
“…In doing so, we highlight interpersonal racial discrimination as a potent criminogenic risk factor contributing to racial disparities in crime. To link discrimination experiences to offending, we draw upon a recently developed social schematic perspective, which theorizes the process through which social factors, such as racial discrimination, influence general offending through cognitive knowledge structures (Simons & Burt, 2011). We also explore the protective effects of two forms of ERS-cultural socialization and preparation for bias-building explicitly on a study of African American males (Burt et al, 2012).…”
mentioning
confidence: 99%
“…The correspondence between the two measures is then calculated (see, for example, Jensen 1972;Matsueda and Anderson 1998;Simons and Burt 2011;Warr and Stafford 1991).…”
Section: Traditional Approaches To Testing Deviant Modelingmentioning
confidence: 99%